2015
DOI: 10.4055/cios.2015.7.1.15
|View full text |Cite
|
Sign up to set email alerts
|

Paratrooper's Ankle Fracture: Posterior Malleolar Fracture

Abstract: BackgroundWe assessed the frequency and types of ankle fractures that frequently occur during parachute landings of special operation unit personnel and analyzed the causes.MethodsFifty-six members of the special force brigade of the military who had sustained ankle fractures during parachute landings between January 2005 and April 2010 were retrospectively analyzed. The injury sites and fracture sites were identified and the fracture types were categorized by the Lauge-Hansen and Weber classifications. Follow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 22 publications
(26 reference statements)
0
8
0
Order By: Relevance
“…Other mechanisms predisposing to injury include double-leg landing, which distributes force to the knees and femurs, and single-leg landing, which distributes force to the ankle and hip [13]. In one retrospective study, the posterior malleolar fracture has been shown to constitute 41% of fractures sustained in parachute landings [10].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other mechanisms predisposing to injury include double-leg landing, which distributes force to the knees and femurs, and single-leg landing, which distributes force to the ankle and hip [13]. In one retrospective study, the posterior malleolar fracture has been shown to constitute 41% of fractures sustained in parachute landings [10].…”
Section: Discussionmentioning
confidence: 99%
“…Imaging studies for ankle injuries sustained during landing frequently show nonspecific soft tissue swelling, reflecting the prevalence of ankle sprains and other soft-tissue injuries in this population. Characterization of the less-frequent parachute-related ankle fracture has been explored in the literature, albeit to a lesser degree [ 10 ]. We present 10 cases of parachute-related ankle fractures sustained by BAC trainees in order to demonstrate the different presentations of this unique traumatic entity.…”
Section: Introductionmentioning
confidence: 99%
“…15 Nevertheless, other mechanisms may also lead this particular ankle fracture. 9 Based on radiography and computed tomography (CT), Haraguchi and collaborators divided the posterior malleolus fractures in three different types: type 1, fracture of the posterolateral portion of the tibia; type 2, fracture of the posterolateral portion of the tibia up to the medial malleolus; type 3, one or more small fragments of the posterior lip of the malleolus. 6 Taking into account that these particular fracture symptoms may simulate an ankle sprain, it is crucial to perform a differential diagnosis examination.…”
Section: Discussionmentioning
confidence: 99%
“…8 Usually, these fractures are related to a specific injury mechanism comprising, plantar flexion in axial load at the moment of ground impact, supination or external rotation of the talus in axial load, or progressive external rotation of the talus. 9 Given the need to standardize the diagnosis and complementary imaging procedures on ankle injuries, Stiell and collaborators created the "Ottawa Ankle Rules", a clinical and radiological decision algorithm aiming to reduce the high number of radiographs made at the ankle joint, often considered unnecessary. 10 This clinical decision model has been widely used in…”
Section: Introductionmentioning
confidence: 99%
“…This repetitive training includes different stages, such as exiting the plane, free-fall and landing. The preliminary training required before skydiving can begin is held at simulation center suitable for all phases (2). To attain and maintain the level of training and skill necessary for the free-fall stage, vertical wind tunnels (VWTs) are used.…”
Section: Introductionmentioning
confidence: 99%